1999
DOI: 10.1518/001872099779656789
|View full text |Cite
|
Sign up to set email alerts
|

Aurally Aided Visual Search in Three-Dimensional Space

Abstract: We conducted an experiment to evaluate the effectiveness of spatial audio displays on target acquisition performance. Participants performed a visual search task with and without the aid of a spatial audio display. Potential target locations ranged between plus and minus 180° in azimuth and from -70° to +90° in elevation. Independent variables included the number of visual distractors present (1,5, 10, 25, 50) and the spatial audio condition (no spatial audio, free-field spatial audio, virtual spatial audio). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
58
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 10 publications
8
58
1
1
Order By: Relevance
“…Experiment 4 was designed to investigate whether the mode of presentation of the auditory cues would affect the efficiency of participants' visual search performance. Previous research suggests that the spatial colocalization of a cue and target event can yield larger performance benefits than when the cue and target are not colocalized (see, e.g., Bolia, D'Angelo, & McKinley, 1999;Ho, Tan, & Spence, 2006;. This is indeed what we found in our final experiment.…”
Section: Tion ( 38) There Was No Significant Effect Of Cue Type [F(supporting
confidence: 88%
See 1 more Smart Citation
“…Experiment 4 was designed to investigate whether the mode of presentation of the auditory cues would affect the efficiency of participants' visual search performance. Previous research suggests that the spatial colocalization of a cue and target event can yield larger performance benefits than when the cue and target are not colocalized (see, e.g., Bolia, D'Angelo, & McKinley, 1999;Ho, Tan, & Spence, 2006;. This is indeed what we found in our final experiment.…”
Section: Tion ( 38) There Was No Significant Effect Of Cue Type [F(supporting
confidence: 88%
“…For example, an earlier study by Bolia et al (1999) showed that the presentation of freefield auditory spatial cues in a visual search task led to rapid search latencies characteristic of parallel search, whereas similar virtual auditory cues, while also resulting in significant reductions in search latencies (as compared with when no sound was presented), nevertheless led to performance that was most consistent with serial search (cf. Roberts, Summerfield, & Hall, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Auditory and tactile cues have also been shown to influence visual search. This has been shown when the auditory or tactile cue was spatially informative (Bolia, D'Angelo, & McKinley, 1999;Jones, Gray, Spence, & Tan, 2008;Rudmann & Strybel, 1999), when the auditory or tactile cue was temporally synchronous with a change in color of the target (Ngo & Spence, 2010;Van der Burg, Cass, Olivers, Theeuwes, & Alais, 2010;Van der Burg, Olivers, Bronkhorst, & Theeuwes, 2008b, Van der Burg, Olivers, Bronkhorst, & Theeuwes, 2009Zannoli, Cass, Mamassian, & Alais, 2012) and when the auditory cue was semantically congruent with the target object (Iordanescu, Grabowecky, Franconeri, Theeuwes, & Suzuki, 2010;Iordanescu, Gravowecky, & Suzuki, 2011;Iordanescu, Guzman-Martinez, Grabowecky, & Suzuki, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This finding indicates that having redundant information can actually speed reaction time (i.e. both verbal and nonverbal/spatial directional cues provide the same information), which is supported by research on multi-modal redundant targets (Bolia, et al, 1999;Gondan, et al, 2005;Tannen, et al, 2004). However, the study did not investigate the effect of an incongruent, or conflicting verbal-spatial directional cue.…”
Section: Introductionmentioning
confidence: 65%
“…Collision avoidance warning systems are an important component of this effort (Ho & Spence, 2005;Wang, Pick, Proctor, & Ye, 2007). The most effective means by which to alert drivers remains a point of debate, but research has shown that spatial auditory cues speed reaction time to stimuli and that multi-modal directional cues can speed reaction time even further (Bolia, et al, 1999;Gondan, et al, 2005;Tannen, et al, 2004). As a result, much research in this field has focused on the spatial nature and modality of warnings.…”
Section: Introductionmentioning
confidence: 99%